The NPC1L1 Gene Exerts a Notable Impact on the Reduction of Low-Density Lipoprotein Cholesterol in Response to Hyzetimibe: A Factorial-Designed Clinical Trial - Liao, Jianwei; Yang, Liyun; Zhou, Luping; Zhao, Hongbin; Qi, Xiao; Cui, Yimin; Ouyang, Dongsheng (Frontiers in Pharmacology, 2022)
Background: Hzetimibe is a novel inhibitor of cholesterol that specifically targets the NPC1L1 gene. Significant inter-individual variability suggests the existence of an abundance of poor responders and non-responders. In addition, the current literature is inconsistent and controversial regarding the potential impact of the Niemann-Pick C1-Like 1 (NPC1L1) gene on low-density lipoprotein cholesterol (LDL-C) reduction. In light of these concerns, we performed a high-quality clinical trial to investigate the specific characteristics of NPC1L1 gene variation on LDL-C reduction. Methods: This was a multicenter, randomized, double-blind, placebo-controlled, clinical trial with a factorial-design. Qualified patients were randomly assigned to 1 of 6 treatments: placebo, hyzetimibe (10 or 20 mg), atorvastatin, and atorvastatin plus hyzetimibe (10 or 20 mg). Fasting blood samples were collected, genotyped, and the concentrations of LDL-C and the targeted drug trough, were determined to investigate the association between NPC1L1 gene expression and the reduction of LDL-C. Results: In total, 727 individuals were initially recruited; of, these 444 were eligible to begin the trial. We identified one SNP (g1679C > G) that exerted significantly different impacts on LDL-C levels. As monotherapy, CC carriers experienced significantly higher reductions in mean LDL-C (-23.99%) than either the GG (-16.45%, P <0.01) or GC (-13.02%, P <0.01) carriers in the hyzetimibe (20 mg) group. In contrast, when co-administrated with atorvastatin, GC carriers experienced greater LDL-C reduction than non-GC carriers (-52.23% vs -45.03%) in the hyzetimibe (20 mg) plus atorvastatin group. Furthermore, the proportions of individuals experiencing a reduction in LDL-C by >50% increased as the dose of hyzetimibe increased from 16.1% to 65.4%. Conclusion: The g1679C > G SNP in the NPC1L1 gene is critical and exerts differential impact on the response to hyzetimibe treatment. Heterozygotic patients respond with poor efficacy when treated by monotherapy, but show good responses in terms of LDL-C reduction when hyzetimibe was co-administered with atorvastatin. To treat hypercholesterolemia in a precise manner with hyzetimibe, it is necessary to identify genotype patients for the g1679C > G SNP. We also highlight the potential necessity for identifying the appropriate subjects to be treated with ezetimibe.